Detecting the Functionality of Executive Motor Task and Motor Imagery Through Electroencephalography (EEG) - (:unkn) unknown (IEEE, 2014)
In this study, electrical activity of the brain is measured to assess the changes due to motor function, namely during motor execution and motor imagery tasks. First group of experiment covers motor execution task which subjects are required to clench the ball according to the direction of right or left arrows whereas in second group of experiment, subjects carried out a motor imaginary task which subjects imagine as if they are clenching the ball with their left or right hand. In motor execution task, subjects were asked to clench a tennis ball according to left or right cue arrow indicating, which hand the subject, should use. In motor imaginary task, subjects were asked to 'imagine' as if they clench a tennis ball according to left or right cue arrow. mu rhythm is the indicator of suppression during motor execution and imagery in alpha band. As a neurophysiologic marker of the electrical activity of the brain, during motor execution mu rhythm is suppressed with a higher rate as opposed to motor imagery. According to our results, it is shown that there is statistical significance between motor movement and motor imagery, in upper alpha band of the power spectral density.
Keywords: EEG; motor execution; motor imagery; mu rhythm; suppression; MU RHYTHM